Merging Prêt-à-Voter and PunchScan - van de Graaf, Jeroen (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2007: Anais do VII Simpósio Brasileiro de Segurança da Informação e de Sistemas Computacionais, 2007)
We describe a variation of Prêt-à-Voter that keeps the same ballot layout but borrows and slightly modifies the underlying cryptographic primitives from Punchscan, substituting the mix network for bit commitments.